A atividade de pesquisa na pós-graduação stricto sensu: uma análise interacionista sociodiscursiva - Souza, Luana Pinheiro (2020)
Initial and continuing teacher education, training practices, literacy practices, textual genres, disciplinary culture and the academic context as a whole have been subject of several studies and discussions in the field of Applied Linguistics in Brazil and abroad that, in line with the theoretical-epistemological and methodological principles of Sociodiscursive Interactionism (BRONCKART, 1999, 2006, 2008), it has provided the investigation and understanding of human development and action through the language practices materialized in the speech texts. However, studies on researchers in the process of formation still need reflection in the context of the academic field and the formative and discursive practices. Thus, this research aims to identify which elements are inherent to the research activity of PhD students, as well as to analyze and interpret how the PhD student understands his research activity and in what way(s) this PhD student perceives himself (or not) as a researcher, and also, how the disciplinary culture influences the perception and understanding of this activity. Based on such questions, it was hypothesized that the emergence in research activity, the tools that the PhD students appropriate for the development of their activities, the others and, still, the notion of academicsocial responsibility are factors that can influence how these PhD students understand their research activities. Since this research is of a qualitative-interpretative nature, the semistructured interview was adopted as an instrument that generates the data that make up its corpus. The analysis of these data was based on the methodological-analytical proposal of textual architecture (MACHADO; BRONCKART, 2009) with an emphasis on two categories: thematic content and person indexes. To this end, text-speeches produced by two researchers, one from the Postgraduate Program in Letters and the other from the Postgraduate Program in Mechanical Engineering at the Federal University of Paraíba, were analyzed. From the analysis of these texts-speeches, it was possible to list a more general thematic content that unfolded into three sub-themes evidenced by the collaborators, namely: emergence in the research activity; formative mediations: tools and others; and notion of academic-social responsibility. Based on the analysis of such content, the results showed that research practice since graduation and the influence of disciplinary culture are significant in the development of research activities that continue in graduate school. In addition, the professors and advisors cited by our collaborators played an important role in “becoming a researcher” for our PhD students, and that the notion of academic-social responsibility is closely related to the way the researcher faces the demands of his activity.